Private Provision of Education : Opportunities for Emerging Markets - Walton, Tom (International Finance Corporation, Washington, DC, 2018)
The private sector plays an important role in emerging market countries with limited education capacity by providing quality schooling at all levels, from early childhood development to tertiary education and lifelong learning. By strengthening connections between education providers and private enterprises, it helps equip students with skills needed for successful employment, thereby creating additional potential for development. Private firms also play multiple roles in supporting public education by publishing learning materials and developing assessment tools and educational software, building and maintaining schools, and enabling financial support for students in need of it. As a result, private firms can help support all education institutions, private or public, and maximize their contribution to education outcomes.